La prueba en el procedimiento constitucional de la acción de protección - Salas, Juan C. (2020)
The Protection Action is a Jurisdictional Guarantee that has become an interesting and peculiar constitutional and legal tool of the Ecuadorian system, to guarantee the nonviolation of rights by actions or omissions by the state as well as individuals. The purpose of this investigation is to carry out a study of the evidence in the procedure of the Jurisdictional Guarantee called Protection Action, the objective is to: Analyze the evidence in the Protection Action procedure, previously carrying out an analysis of the evidence of the jurisdictional processes, to then make a study on the regulation of evidence in nonconstitutional and constitutional matters, to finally land on an analysis of the test in the procedures referring to the Protection Action. The problematic situation arises from the question: How is Evidence regulated in the Protection Action procedure?, and it is concluded that Art. 16 of the Organic Law of Jurisdictional Guarantees and Constitutional Control regulates evidence in a general way to evidence due to the Protection Action Procedure and also the importance of knowing the importance of the proof compared to the fact of proving a violation or not of a constitutional right.